The Relationship between Principal's Leadership and Teacher's Work Spirit on Learning Motivation of State High School Students in West Seram District - Lani Corinta; R. Kempa; S. Rumfot (Peneliti.net, 2022)
The principal's leadership provides work motivation to increase teacher work productivity and student learning outcomes. According to Mulyasa (2009: 98) the principal has at least a role and function as an Educator, Manager, Administrator, Supervisor, Leader, Innovator and Motivator (EMASLIM).